PERAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL KALIMANTAN TENGAH DALAM UPAYA MENURUNKAN ANGKA PERNIKAHAN DINI DI KALIMANTAN TENGAH - Latifah, Winda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to analyze the role of the National Population and Family Planning Board (BKKBN) of Central Kalimantan in reducing early marriage rates, along with its supporting and inhibiting factors. The research uses a qualitative case study approach conducted from December 2024 to March 2025 in Central Kalimantan. Data were collected through observations and interviews with the BKKBN Secretary, youth resilience program officers, family planning field officers (PLKB), and adolescents involved in early marriage. The data were analyzed using an interactive model, including data reduction, presentation, and conclusion drawing, and verified through source and method triangulation. The findings show that BKKBN implements several programs such as PUP (Marriage Age Maturity), GenRe (Planned Generation), and BKR (Adolescent Family Development), supported by local governments, family planning agencies (OPD KB), village governments, and PLKB. However, early marriage rates remain high due to lack of educational media, economic issues, promiscuity, and difficult access to target areas.